Low-tech, high-value: Electrocardiographic markers of left ventricular dysfunction in non-ischemic cardiomyopathy - Ghosh, Soumik; Tandon, Arjun; Kulshreshtha, Srashti; Kumar A, Lava; Amit, Kumar; Agrawal, Vikas (Heart Science Journal, 2025)
Background: Electrocardiography (ECG) is a widely accessible, cost-effective diagnostic tool, particularly valuable in resource-limited settings where echocardiography is unavailable. Identifying ECG parameters that reflect left ventricular (LV) systolic dysfunction could enable earlier detection and intervention in patients with non-ischemic cardiomyopathy (NICM). Objectives: To evaluate the correlation between ECG parameters—QTc duration, QRS duration, morphology, voltage, and axis—and left ventricular ejection fraction (LVEF) in NICM patients with reduced ejection fraction (REF), and to assess their potential as surrogate markers of LV systolic function. Methods: A cross-sectional study was conducted on 140 NICM patients (LVEF ≤40%) confirmed by echocardiography and angiography. Clinical, biochemical, and ECG data were collected. Pearson’s correlation and ANOVA were used to assess associations between ECG variables, mitral regurgitation (MR) severity, hemoglobin levels, and LVEF. Results: QTc duration showed a significant inverse correlation with LVEF (r = –0.428, p = 0.001). Hemoglobin levels were positively correlated with LVEF (r = 0.175, p = 0.039). The presence of mitral regurgitation was associated with lower LVEF (p = 0.029), with a trend toward further decline as severity increased. Conclusions: Prolonged QTc was strongly associated with reduced LVEF in patients with non-ischemic cardiomyopathy. As ECG is inexpensive and widely available, QTc may provide a simple surrogate marker to aid in identifying LV dysfunction, especially in resource-limited settings. Larger prospective studies with outcome data are needed to validate its prognostic role.